Probable ways of Tannery's solid and liquid waste management in Bangladesh : an overview - Saha, Biraj (Array, 2021)
The leather industry has been marked as a top-priority sector due to its potential growth and economical contribution in Bangladesh. However, these industries are unable to meet the compliance issue due to the environmental pollution. Leather processing is a complex process based on chemicals and mechanical methods. A substantial amount of solid and liquid wastes is generally produced during the production of leather. As most of the tanneries do not have a central effluent treatment plant and advanced management technologies, they produce 20000 m3 of liquid waste and 232 tonnes of solid waste per day in Bangladesh, which poses a significant risk to the environment and human health unless it gets well treated. In this modern era, it is indispensable to implement new technologies to treat liquid waste properly as well as innovative disposal techniques for solid waste to reduce pollution and health hazards. This study, by using a non-systematic approach based on literature reviews, is designed to summarize the kinds of solid and liquid waste management techniques around the world which should be implemented in the tanneries of Bangladesh to mitigate environmental pollution. We hope that this study can be a great resource and provide a pathway for leather industries in Bangladesh to get familiar with effective treatment technologies of solid and liquid wastes.